New insights on Neolithic food and mobility patterns in Mediterranean coastal populations. Issue 2 (18th June 2020) - Goude, Gwenaëlle; Salazar‐García, Domingo C.; Power, Robert C.; Rivollat, Maïté; Gourichon, Lionel; Deguilloux, Marie‐France; Pemonge, Marie‐Hélène; Bouby, Laurent; Binder, Didier
Abstract: Objectives: The aims of this research are to explore the diet, mobility, social organization, and environmental exploitation patterns of early Mediterranean farmers, particularly the role of marine and plant resources in these foodways. In addition, this work strives to document possible gendered patterns of behavior linked to the neolithization of this ecologically rich area. To achieve this, a set of multiproxy analyses (isotopic analyses, dental calculus, microremains analysis, ancient DNA) were performed on an exceptional deposit ( n = 61) of human remains from the Les Bréguières site (France), dating to the transition of the sixth to the fifth millennium BCE. Materials and Methods: The samples used in this study were excavated from the Les Bréguières site (Mougins, Alpes‐Maritimes, France), located along the southeastern Mediterranean coastline of France. Stable isotope analyses (C, N) on bone collagen (17 coxal bones, 35 craniofacial elements) were performed as a means to infer protein intake during tissue development. Sulfur isotope ratios were used as indicators of geographical and environmental points of origin. The study of ancient dental calculus helped document the consumption of plants. Strontium isotope analysis on tooth enamel ( n = 56) was conducted to infer human provenance and territorial mobility. Finally, ancient DNA analysis was performed to study maternal versus paternal diversity within this Neolithic group ( n = 30). Results: Stable isotope ratios for human bones range from −20.3 to −18.1‰ for C, from 8.9 to 11.1‰ for N and from 6.4 to 15‰ for S. Domestic animal data range from −22.0 to −20.2‰ for C, from 4.1 to 6.9‰ for N, and from 10.2 to 12.5‰ for S. Human enamel 87 Sr/ 86 Sr range from 0.7081 to 0.7102, slightly wider than the animal range (between 0.7087 and 0.7096). Starch and phytolith microremains were recovered as well as other types of remains (e.g., hairs, diatoms, fungal spores). Starch grains include Triticeae type and phytolith includes dicotyledons and monocot types as panicoid grasses. Mitochondrial DNA characterized eight different maternal lineages: H1, H3, HV (5.26%), J (10.53%), J1, K, T (5.2%), and U5 (10.53%) but no sample yielded reproducible Y chromosome SNPs, preventing paternal lineage characterization. Discussion: Carbon and nitrogen stable isotope ratios indicate a consumption of protein by humans mainly focused on terrestrial animals and possible exploitation of marine resources for one male and one undetermined adult. Sulfur stable isotope ratios allowed distinguishing groups with different geographical origins, including two females possibly more exposed to the sea spray effect. While strontium isotope data do not indicate different origins for the individuals, mitochondrial lineage diversity from petrous bone DNA suggests the burial includes genetically differentiated groups or a group practicing patrilocality. Moreover, the diversity of plant microremains recorded in dental calculus provide the first evidence that the groups of Les Bréguières consumed a wide breadth of plant foods (as cereals and wild taxa) that required access to diverse environments. This transdisciplinary research paves the way for new perspectives and highlights the relevance for novel research of contexts (whether recently discovered or in museum collections) excavated near shorelines, due to the richness of the biodiversity and the wide range of edible resources available.